Post-Encephalitic Parkinsonism and Sleep Disorder Responsive to Immunological Treatment: A Case Report. (October 2016) - Brunetti, Valerio; Testani, Elisa; Iorio, Raffaele; Frisullo, Giovanni; Luigetti, Marco; Di Giuda, Daniela; Marca, Giacomo Della
We describe a 70-year-old man who, after a viral encephalitis associated with pneumonia, progressively developed a parkinsonism associated with lethargy. Encephalitis manifested with persistent hiccups, seizures and impairment of consciousness. After 2 weeks, the initial neurologic symptoms subsided and the patient progressively developed movement disorders (rigidity and bradykinesia, resistant to L-DOPA), lethargy and behavioral hypersomnia. Magnetic resonance imaging showed thalamic and hippocampal signal abnormalities, immunohistochemistry on a mouse brain substrate revealed serum autoantibodies binding to the brainstem neuropil. Polysomnographic monitoring was consistent with a very severe disruption of sleep: the sleep-wake cycle was fragmented, and the NREM-REM ultradian cycle was irregular. Intravenous immune globulin therapy resulted in the complete reversal of the movement and the sleep disorders. Our observation confirms that parkinsonism and sleep disorders may be consequences of encephalitis, that an immune-mediated pathogenesis is likely, and, consequently, that immunotherapy can be beneficial in these patients. The polysomnographic monitoring suggests that lethargia, rather than a mere hypersomnia, is the result of a combination between sleep disruption and altered motor control.